New replacement name for Kyra Zanol, 2011 (Hemiptera: Cicadellidae: Deltocephalinae) - Yang, Wei-Cheng (Zootaxa, 2017)
The leafhopper genus Kyra was established by Zanol (2011) with Kyra paranaigua Zanol, 2011 as its type species, and additional new species, Kyra guaira Zanol 2011, and one previously described species (transferred to the genus from Bahita Oman): K. umbrina (Linnavuori, 1955). The genus belongs to the tribe Bahitini Zahniser & Dietrich, 2013 of subfamily Deltocephalinae (Hemiptera: Cicadellidae). Until now, there have been no further reports on this genus, and all species are recorded only from Brazil.